Uwagi o zasadach wymiaru kary w polskich kodeksach karnych - Bojarski, Tadeusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This paper covers issues related to the principles of imposing penalties. Apart from their considerable practical significance, these directives are closely related to the theory and philosophy of punishment. The purpose of these comments is a simple indication of the assumptions underlying the principles of imposing penalties, including the way of their evolution in Polish criminal law since 1932. The choice of theme is justified by the importance, the true wealth of problems that occur here and the theoretical but also research interests of Professor Tomasz Kaczmarek. The author wants to emphasize that the evolution of the principles of imposing penalties from the first statutory regulations runs properly. A clear tendency in the Polish legislature was consolidation and expansion of these directives, which remain compatible with the new less repressive criminal and sanctions policy. The Penal Code currently in force provided also appropriate lower limits of penalties.
Keywords: wymiar sprawiedliwości karnej; kara; teorie kary; zasady wymierzania kar; cele kary